2021
DOI: 10.1080/02670844.2021.1884332
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical, kinetic and corrosion properties of borided AISI 304, AISI 420 and AISI 430

Abstract: In this study, three different types of stainless steels, AISI 304, AISI 420, and AISI 430 were pack borided under 850 °C-925 °C-1000 °C for 2, 4, and 6 h, respectively. Morphologies of coating were investigated by optical and scanning electron microscope (SEM). The maximum layer hardness was determined to be 1736 HV 0.05 , 1659 HV 0.05 , and 1572 HV 0.05 for AISI 304, AISI 420, and AISI 430, respectively. Phases formed on the layer were determined by X-ray analysis (XRD) to confirm the presence of FeB, Fe 2 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
(57 reference statements)
2
7
1
Order By: Relevance
“…The boronized specimen at the boronizing temperature of 1173 K with 4 h exposure time was subjected to basic X-ray diffraction (XRD) analysis, and only two iron borides, namely iron monoboride and diiron boride, were revealed. On the other hand, Turker Turkoglu and Ay [ 62 ] discovered, through XRD analysis, the presence of iron monoboride, diiron boride and chromium monoboride on the boron surface of the sample at 1273 K for 6 h. According to their research, they agree with our results.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The boronized specimen at the boronizing temperature of 1173 K with 4 h exposure time was subjected to basic X-ray diffraction (XRD) analysis, and only two iron borides, namely iron monoboride and diiron boride, were revealed. On the other hand, Turker Turkoglu and Ay [ 62 ] discovered, through XRD analysis, the presence of iron monoboride, diiron boride and chromium monoboride on the boron surface of the sample at 1273 K for 6 h. According to their research, they agree with our results.…”
Section: Resultssupporting
confidence: 90%
“…Likewise, they revealed that the growth of boronized coatings could increase by a factor of two when using microwave heating instead of conventional heating methods like an oven. In another interesting study, Kayali and Mertgenç [72] applied the thermochemical boronizing treatment to an AISI 303 stainless steel in a temperature range from 1173 K to 1223 K. Their findings showed that the minimum energy of iron borides is around 236.5 kJ•mol −1 , which is consistent with other reported studies [55,62,75]. In other research, Kayali [64] hardened different stainless steels (AISI 420, AISI 304 and AISI 304L) by thermochemical boronizing treatment employing the powder-pack technique in the temperature range from 1123 K to 1223 K, and, considering that the boronized coatings obey the parabolic growth law, was able to determine the minimum energies for each steel (Q AISI 420 = 206.1 kJ•mol −1 , Q AISI 304 = 234.6 kJ•mol −1 and, Q AISI 304L = 222.8 kJ•mol −1 ).…”
Section: Derivation Of the Activation Energies Of Boron In Feb And Fe...supporting
confidence: 78%
See 1 more Smart Citation
“…Boronized components deliver better performance as compared to those processed from other methods. Boronizing produces a diffusion layer thermo-chemically that contains borides that are harder (1800-3000 HV) than compounds resulting from other surface treatments [4]. Thus boronized steels have potential to deliver improved performance in severe environments.…”
Section: Introductionmentioning
confidence: 99%
“…), and duplex (Ferritic-Austenitic) stainless steels (1.4362, 1.4507 etc.) (Türkoğlu and Ay 2021). After giving brief information about sheet metals, especially stainless steels, some of the scientific studies in this field are briefly summarized.…”
Section: Introductionmentioning
confidence: 99%